Evaluation of left atrial function by speckle tracking echocardiography in patients with systemic lupus erythematosus. (April 2016) - Dai, M; Li, K L; Qian, D J; Lu, J; Zou, Y H; Cao, Y X; Yang, Z Y; Wang, R X
Left atrial (LA) function plays a key role in maintaining optimal cardiac output. Left ventricular diastolic dysfunction (LVDD) has been reported in systemic lupus erythematosus (SLE), but whether LA functional abnormalities also occur in patients with SLE is unknown. Toward this aim we evaluated left atrial function and volume by strain and strain rate derived from speckle tracking echocardiography (STE) and their associations with LVDD. Sixty SLE patients were compared with age- and gender-matched normal controls. The LA strain (S) and strain rate (SR) during systole, early diastole and late diastole (SRs, SRe and SRa, respectively) were measured by STE. The LA volume index (LAVI), traditional parameters of LA and left ventricular diastolic function also were analysed. Global strain and positive SRe were significantly reduced in the SLE group compared with the control group (26.2% ± 9.5% vs 32.5% ± 9.8% and −2.4 ± 1.0 s −1 vs −3.1 ± 1.2 s −1, both p  < 0.05). The SRs in the SLE and control groups were not significantly different (2.1 ± 0.7 s −1 vs 2.4 ± 0.8 s −1, p  = 0.2). The positive SRa was increased in the SLE group compared with the control group (−2.1 ± 0.8 s −1 vs −1.6 ± 0.5 s −1, p  < 0.05) and the LAVI was larger in the SLE group than in the control group (32.4 ± 8.0 vs 25.8 ± 7.1 ml/m 2, p  < 0.001). Patients with SLE exhibiting varying grades of LVDD displayed significant differences in LA parameters, including LAVI, SRs, SRe and SRa (all p  < 0.05). Multivariate linear analysis additionally revealed that SLICC/ACR damage index (SDI) was independently and inversely associated with global strain, SRs and positive SRe. LA functions were changed in SLE patients, demonstrating impairment in conduit function, decrease in storage function and increase in pump function. Meanwhile, the magnitude of this impairment was predictively associated with the severity of LVDD. The results from this study demonstrate that STE is capable of detecting various aspects of LA functional impairment during SLE progression, and should be further explored as a diagnostic tool for improving the outcomes of SLE patients.